Unraveling Of Urinary Disorders to Adenomyosis and Dysmenorrhea - darto, darto; Anggraeni, Asih; Ngudi Insan Ksyatria, Yudhistira; Alifa, Rosita; Farras Wahdan, Arib; Retno Budihastuti, Uki; Laqif, Abdurahman; Melinawati, Eriana; Prakosa, Teguh; Udiyanto, Hermawan; Priyanto, Heru; Angelia Ratnasari, Affi (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objective : This study aims to explore the relationship between micturition disorders and adenomyosis and dysmenorrhea and provide insight into the factors associated with the severity of LUTS symptoms in these conditions. Methods : This study was a descriptive qualitative study. We retrospectively collected medical record data from the Obstetrics Gynecology Outpatient Ward of Dr. Moewardi Surakarta General Hospital in the period January 2021 to May 2023. The results of this study analyzed using Pearson correlation analysis if normally distributed and using Mann-Whitney if not normally distributed, thus, statistically analyzed. Results: There is a significant relationship between adenomyosis and dysmenorrhea on urinary disorders (p value of 0.016) where urinary disorders are found to be more severe in adenomyosis patients with dysmenorrhea. Conclusion : Lower urinary tract symptoms are common in symptomatic adenomyosis patients and greatly affect the patient's quality of life. Dysmenorrhea can be a potential risk factor that increases the occurrence of moderate to severe LUTS. Keywords: adenomyosis; dysmenorrhea; urinary disturbance.